Cinematically speaking : the orality-literacy paradigm for visual narrative - Sheila J. Nayar (Sage, 2010)
Most people think of film narrative in fundamentally visual terms. But what if visuality is only one component of a larger epistemic framework for how film narrative works? In this book, Sheila J. Nayar argues just that, laying out the comprehensive terrain for what has already been described as a controversial new theory of cinematic literacy.